2020
DOI: 10.1016/j.jtemb.2020.126453
|View full text |Cite
|
Sign up to set email alerts
|

Geographical and seasonal variation in iodine content of cow’s milk in the UK and consequences for the consumer´s supply

Abstract: Background. Dairy products provide a crucial source of dietary iodine for the majority of the UK population, contributing approximately 30-40 % of daily intake. Fluctuations in the iodine content of purchased milk both seasonally and annually implies potential fragility of iodine supply likely through fluctuating supplementation practices in cow herds. We set out to establish the level of national variation in herds and identify factors which might impact milk iodine content. Methods. Milk samples were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
1
10
0
1
Order By: Relevance
“…In this context Hejtmankova et al (2006) observed that milk iodine concentration in winter was between 147 μg/kg and 605 μg/kg compared to that in the summer season ranging from 35 μg/kg to 484 μg/kg. This effect of the season was observed also by other authors (Schone and Rajendram 2009;van der Reijden et al 2017;Coneyworth et al 2020). The ef- (Flachowsky et al 2014).…”
Section: Farm Management and Animal Keepingsupporting
confidence: 80%
See 1 more Smart Citation
“…In this context Hejtmankova et al (2006) observed that milk iodine concentration in winter was between 147 μg/kg and 605 μg/kg compared to that in the summer season ranging from 35 μg/kg to 484 μg/kg. This effect of the season was observed also by other authors (Schone and Rajendram 2009;van der Reijden et al 2017;Coneyworth et al 2020). The ef- (Flachowsky et al 2014).…”
Section: Farm Management and Animal Keepingsupporting
confidence: 80%
“…This fact might point to another important source of iodine, dairy milk and dairy products (van der Reijden et al 2019), which already cover a substantial portion of adults' dietary iodine requirements in countries like USA (Abt et al 2018), United Kingdom (Coneyworth et al 2020), Ireland (O'Kane et al 2018 and Norway (Troan et al 2015). Milk and milk products as a significant source of iodine in human nutrition are discussed in another part of the review.…”
Section: Iodine Requirementsmentioning
confidence: 99%
“…UK milk iodine concentration, however, can vary with season (e.g. milk has a higher iodine concentration in winter than in summer as a result of varying farming practice) (11,13) .…”
mentioning
confidence: 99%
“…Os resultados aqui obtidos são importantes ao considerar que o efeito foi semelhante ao de produtos convencionais, considerando que esses apresentam alguns inconvenientes na sua utilização, como indução de resistência aos biocidas (Fitzpatrick,et al, 2016 ), e a presença de resíduos no leite, sendo veiculados para bezerros ( Van der Reijden, et al, 2018),e para humanos (Ahvanooei, et al, 2021;Ahvanooei, et al, 2020;Coneyworth, et al, 2020;Van der Reijden, et al, 2019), conforme pesquisas que relatam presença de iodo.…”
Section: Resultsunclassified